MEDIA SENI SEBAGAI SARANA MELEPASKAN STRES PARA IBU PKK CILINCING - Michiko, Runi; Jacqualyne Gavrilla Kumayas; Syiefa Atharida Pertiwi; Denrich Suryadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
Cilincing subdistrict, located in Cilincing District, North Jakarta City. Cilincing subdistrict has a family welfare promoter that does activities for children and women. Family welfare promoters consist of housewives who spare their time between family and duties for humanity. As a mother that is also active in family welfare promotion, they experience mental pressure such as stress. Stress is an impact for taking care of family and welfare promoter activities.. The purpose of this activity is to improve the mental health of family welfare promoters. The number of our respondents was 13 people. The measuring instrument used was the Perceived Stress Scale Version 10 (PSS-10). Based on PSS-10 data processing, the result was 19, which means they experience moderate stress. In dealing with stress, material about stress and doing art activities was given to express the emotion. This humanity project was carried out for 18 days, from Tuesday, February 18, 2025, to Tuesday, April 15, 2025. On 18 February we followed and observed their activities. The intervention was carried out within 2 meetings. The intervention was carried out in 2 meetings on Tuesday, April 8, 2025, by providing a pretest, material on stress, and painting. Then the second meeting on Tuesday, April 15, 2025, by providing material on emotional management, painting, and a posttest. The results showed that there was no significant decrease in stress level, with the mean score decreasing only slightly from 19 to 18.5, which still falls within the moderate range. Therefore, it can be concluded that the activity implemented was not effective. Factors contributing to this ineffectiveness included a lack of cooperation, insufficient rapport, limited understanding of the activity’s objectives, and time to conduct the activity, which led to PKK members being unwilling to open up to the project facilitators. ABSTRAK Kelurahan Cilincing yang terletak di Kecamatan Cilincing, kota Administrasi Jakarta Utara memiliki beberapa kegiatan salah satunya program PKK yang banyak melakukan kegiatan pemberdayaan bagi Anak dan Perempuan. PKK Kelurahan Cilincing terdiri dari para ibu rumah tangga yang membagi waktu antara keluarga dan tugas kemanusiaan. Sebagai ibu dan juga aktif di kegiatan PKK, maka para ibu mengalami tekanan mental tersendiri, yaitu stres. Stres tersebut merupakan dampak tanggung jawab rumah tangga dan sekaligus juga tanggung jawab menjadi anggota PKK. Tujuan dari kegiatan ini adalah meningkatkan kesehatan mental ibu - ibu PKK. Jumlah responden adalah 13 orang. Alat Ukur yang digunakan adalah Perceived Stress Scale Versi 10 (PSS-10). Berdasarkan olah data PSS-10, didapatkan hasil mean sebesar 19 yang memiliki arti bahwa ibu - ibu PKK mengalami kondisi stress tingkat sedang. Dalam mengatasi stres tersebut dilakukan penyampaian materi mengenai stres dan melakukan aktivitas seni sebagai tempat untuk mengekspresikan emosi. PKM dilaksanakan selama 18 hari pada Selasa 18 Februari 2025 sampai dengan Selasa 15 April 2025. Tanggal 18 Februari mengikuti kegiatan PKK dan mengobservasi. Aktivitas seni dilakukan dalam 2 pertemuan pada hari Selasa 8 April 2025 dengan pemberian pretest, materi mengenai stres, dan melukis. Pertemuan kedua dilaksanakan pada hari Selasa 15 April 2025 dengan pemberian materi mengenai pengelolaan emosi, melukis, dan posttest. Hasilnya ditemukan tidak ada penurunan tingkat stres dari mean sebesar 19 menjadi 18.5 dan masih dalam taraf sedang sehingga dapat disimpulkan bahwa kegiatan yang dilakukan tidak efektif. Kurangnya kerjasama, rapport, kurangnya pemahaman terhadap tujuan kegiatan, dan waktu untuk melaksanakan kegiatan sehingga para ibu anggota PKK tidak terbuka kepada pelaksana PKM.